(untitled) - Sedliak, Marian; Sulgan, Marian (Doprava a spoje, 2012)
This contribution presents the theoretical cost model for the suitability assesment of the direct Just-in-Time deliveries. The model contains all main cost type that are relevant when considering the change of the supply system.